Mullaway - Nicholls, Bronwen (Ringwood, Victoria : Penguin Books, 1986)
When Mum has to suddenly and permanently take to her bed, sixteen-year-old Mully finds herself in charge of a muddled household. In becoming The Mum, Mully uncovers startling truths about each of her family. And she also discovers that taking on her mother's role isn't the walkover she expected.
"Published with the assistance of the Literature Board of the Australia Council'.
White
For young adults.
Keywords: Australian